Legal Atlantic Forest (Mata Atlântica Legal): integrating biogeography to public policies towards the conservation of the biodiversity hotspot - Cunha, André de Almeida; Carla Bernadete Madureira; Bouchardet da Fonseca, Gustavo Alberto (Sustainability in Debate, 2019)
The Atlantic Forest (AF) is one of the most biodiverse and threatened biomes on the planet, but the existence of two official boundaries (AF Biome and Domain ”“ AF Law) causes uncertainties, with consequences for public policies and the conservation of remnants. In order to understand the biogeography and its influence for protection of the AF, the areas of the two boundaries and the overlap with states and ecoregions they occupy were compared. Our results, supported by the literature, indicate that the Legal boundary is broader and more representative of AF’s current and evolutionary heterogeneity and diversity, and provides a more adequate legal basis for its conservation and sustainable use, especially in the northeast region, where the biggest difference between both limits were encountered. Thus, the term Legal Atlantic Forest should be increasingly used, in order to reinforce the full application of laws governing the protection and sustainable use of the biome.